Religion and aging: intercultural and interdisciplinary explorations - Bieler, Andrea; Stracke-Bartholmai, Matthias; Veddeler, Angelika (ContactZone, 2017)
Religion and aging in international and intercultural perspectives : mapping the field / Andrea Bieler and Matthias Stracke -- Interdisciplinary horizons. The longevity revolution : global developments and ways forward / Ina Voelcker and Alexandre Kalache -- Themes in contemporary behavioral and social gerontology / Hans-Werner Wahl -- Debunking myths of aging : implications for church participation of older adults / Jenny S. Y. Lee and Helene H Fung -- When religion matters : aging, health and care in Indonesia and Tanzania / Peter van Eeuwijk -- Theological contributions.-- Discourse on religion and aging : integrating theological and intercultural perspectives / Ralph Kunz -- A paradox of life : finding meaning in aging : horizons in theological anthropology / Angel F Mendez-Montoya OP -- And Sarah laughed : observations on Bible, aging and postcoloniality / Musa Dube -- "Who do you say that I am?" : people living with dementia in medical de-constructions and liturgical reconstructions and play / Drea Frochtling -- Concepts, challenges and innovative practice. -- Emerging discourse on aging in the United Evangelical Mission Angelika Veddeler -- Diaconic challenges in elderly care on three continents -Indonesia, Germany, Tanzania and the Philippines / Klaus Poschel -- Protagonism and the role of older people in policy-making - a bottom-up approach / Ina Voelcker -- "With this Alzheimer thing you can't walk alone : walking with and supporting people living with dementia / Drea Frochtling -- Religion and aging in international and intercultural perspectives : a conference commentary and research prospects from a diaconic perspective / Reate Hofmann
"This volume gathers the revised papers of a conference in Wuppertal in December 2015." - Preface
Keywords: Konferenzschrift -- 2015 -- Wuppertal; Religion; Altern; Evangelische Soziallehre; Sozialpolitik; Soziokultur; Alter; Alternde Bevölkerung; Gesellschaft; Evangelische Theologie; Praktische Theologie; Interdisziplinarität